The Influence of Live Streaming and Online Customer Reviews on Consumer Purchase Interest in the Tiktok Shop Feature (Case Study of Pamulang District Community) - Hendra Dwi Prasetyo (Transpublika Publisher, 2025)
The primary objective of the study is to analyse how live streaming and online customer reviews influence consumer interest in making purchases at TikTok Shop. A descriptive quantitative research approach was employed, involving a questionnaire administered to 100 participants from the Pamulang District. The sampling method utilised purposive sampling, with participants required to be at least 18 years old and have made purchases at TikTok Shop. The findings revealed that both live streaming and online customer reviews had a significant positive impact on buying interest at TikTok Shop within the Pamulang District community, both individually and collectively. According to the coefficient of determination, the independent variables accounted for 53.2% of the variability in purchase intention, with the remainder being influenced by unexamined factors. The implications of this study indicate that live streaming-based marketing strategies and the provision of online customer reviews are effective in increasing buying interest on social media, especially on the TikTok Shop platform. This research supports the importance of utilizing interactive features to strengthen consumer trust and product attractiveness in the e-commerce market.